2024
DOI: 10.1002/ece3.10915
|View full text |Cite
|
Sign up to set email alerts
|

The influence of incubation temperature on offspring traits varies across northern and southern populations of the American alligator (Alligator mississippiensis)

Christopher R. Smaga,
Samantha L. Bock,
Josiah M. Johnson
et al.

Abstract: Maternal provisioning and the developmental environment are fundamental determinants of offspring traits, particularly in oviparous species. However, the extent to which embryonic responses to these factors differ across populations to drive phenotypic variation is not well understood. Here, we examine the contributions of maternal provisioning and incubation temperature to hatchling morphological and metabolic traits across four populations of the American alligator (Alligator mississippiensis), encompassing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…Fish are poikilothermic animals (cold-blooded); they show a wide range of temperature tolerance, and their reproductive processes are known to be sensitive to water temperatures [6,7]. The important role of water temperature in sex determination in fish may be due to temperature fluctuations known to occur during embryonic development in extreme environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish are poikilothermic animals (cold-blooded); they show a wide range of temperature tolerance, and their reproductive processes are known to be sensitive to water temperatures [6,7]. The important role of water temperature in sex determination in fish may be due to temperature fluctuations known to occur during embryonic development in extreme environments.…”
Section: Introductionmentioning
confidence: 99%
“…The European seabass (Dicentrarchus labrax) is a gonochoristic species that does not display secondary sex morphological characters. Furthermore, it exhibits obvious sex-linked growth: it has been observed that females grow faster and reach a larger size than males [7][8][9][10]. Females of this species are observed to be about 30% heavier than the males from 300-400 days after hatching (dph) until over 1000 dph [9].…”
Section: Introductionmentioning
confidence: 99%